2007
DOI: 10.1084/jem.20071069
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for complement factor H–linked age-related macular degeneration

Abstract: Nearly 50 million people worldwide suffer from age-related macular degeneration (AMD), which causes severe loss of central vision. A single-nucleotide polymorphism in the gene for the complement regulator factor H (FH), which causes a Tyr-to-His substitution at position 402, is linked to ∼50% of attributable risks for AMD. We present the crystal structure of the region of FH containing the polymorphic amino acid His402 in complex with an analogue of the glycosaminoglycans (GAGs) that localize the complement re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
213
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(227 citation statements)
references
References 30 publications
12
213
0
2
Order By: Relevance
“…The P(r) curve turned out to be sensitive to the bending of this fragment as well as the presence of dimers. The final bent scattering model for SCR-6/8 showed good agreement with the crystal structure of SCR-6/8 that was published afterwards, even though the crystallographers unfortunately did not reference the prior scattering structure determination of SCR-6/8 (Prosser et al 2007).…”
Section: Complement Structures By Constrained Modellingsupporting
confidence: 57%
“…The P(r) curve turned out to be sensitive to the bending of this fragment as well as the presence of dimers. The final bent scattering model for SCR-6/8 showed good agreement with the crystal structure of SCR-6/8 that was published afterwards, even though the crystallographers unfortunately did not reference the prior scattering structure determination of SCR-6/8 (Prosser et al 2007).…”
Section: Complement Structures By Constrained Modellingsupporting
confidence: 57%
“…Polymorphisms in AP proteins C3, fB, and fH strongly influence risk for AMD with quoted odds ratios for homozygotes of 3.51-7.4 for fH Y402H (11,14), 2.6 for C3 R102G (19), 0.36 for fB R32Q (16), and 0.54 for fH V62I (11); each also influences risk for other diseases and/or infections, implying that small changes in AP proteins can dramatically affect health. fH Y402H likely alters capacity of fH to bind surfaces (27,28), but the reasons why other AP polymorphisms influence disease susceptibility were unknown until our demonstration that fB R32Q and fH V62I directly impacted on AP activation and amplification (29,34). Association of the common C3 polymorphism (C3S/F; C3 R102G ) with disease has been recognized for decades, but the molecular basis was enigmatic.…”
Section: Discussionmentioning
confidence: 98%
“…The fH 402H risk variant had no direct effect on fH AP regulation but influenced binding to sialylated surfaces (27,28). The AMD-protective variant, fB 32Q , formed AP convertase less efficiently, whereas the protective variant fH 62I bound C3b more strongly and was a better cofactor for fI inactivation (29).…”
mentioning
confidence: 95%
“…SOS inhibits the FH/FhbB interaction in a dose-dependent manner. Although SOS binds to at least three sites on FH, co-crystallization of SOS with a CCP6 -8 construct revealed that SOS hydrogen bonds with K405 FH (46).…”
Section: Discussionmentioning
confidence: 99%
“…To further validate the FhbB/CCP6 -8 interaction, competitive binding analyses were conducted using SOS. SOS is a GAG analog that interacts with a large positively charged groove within CCP6 -8 (46). SOS inhibited FhbB binding to FH in a dose-dependent manner (Fig.…”
Section: Mutagenesis Studies Of the Fhbb/fh Bindingmentioning
confidence: 94%